Harmine alleviates LPS-induced acute lung injury by inhibiting CSF3-mediated MAPK/NF-κB signaling pathway - Yihui Zhai; Kejie Chen; Zichuang Xu; Xiaojian Chen; Jiaying Tong; Yeying He; Chaoyue Chen; Meiqing Ding; Guang Liang; Xiaohui Zheng (Respiratory Research)
Abstract Background Acute lung injury (ALI) is a life-threatening inflammatory lung disease that lacks safe and effective treatment strategies. Harmine, an alkaloid derived from Peganum harmala L plants, exhibits anti-inflammatory activity. However, the protective effect of harmine against ALI and its underlying mechanism remain unknown. This study aimed to elucidate the therapeutic effects and molecular mechanisms of harmine against ALI. Methods The therapeutic effects of harmine were assessed in LPS-induced ALI mice. Serum, bronchoalveolar lavage fluid (BALF), lung tissues were routinely analyzed to evaluated disease severity. The anti-inflammatory mechanism was elucidated in LPS-simulated RAW264.7 cells using a series assays, including RNA-seq, gene silencing, immunofluorescence, western blotting, co-immunoprecipitation and bioinformatic analysis. The biological safety of harmine was determined both in vitro and in vivo through cytotoxicity test, long-term cell proliferation test, acute toxicity test in mice, and assessments of liver and kidney function and structural changes. Results The results showed that harmine inhibited the expression and secretion of LPS-induced inflammatory factors (IL-6, IL-1β and TNF-α) and reduced inflammatory cell infiltration in the lungs, resulting in alleviated LPS-induced histopathological changes and injury in mice. Mechanically, the findings revealed that harmine does not disrupt the TLR4-MD2 interaction but instead attenuates inflammation by suppressing CSF3 transcription and expression, leading to the inhibition of the MAPK/NF-κB signaling pathway activation induced by LPS stimulation. Additionally, both in vitro and in vivo studies demonstrated that harmine administration does not exhibit obvious cytotoxicity or long-term cell proliferation inhibition, nor does it cause functional or organic lesions the liver and kidney in mice, or other acute toxic effects. Conclusions These findings elucidated that the anti-inflammatory activity of harmine was achieved through the CSF3-mediated inactivation of the MAPK/NF-κB signaling pathway, suggesting that harmine could serve as a promising therapeutic drug for ALI and other inflammatory diseases.